ANALISIS PENERAPAN PSAK 45 MENGENAI PELAPORAN KEUANGAN ENTITAS NIRLABA PADA GEREJA KRISTEN JAWA UNGARAN - RAHMAT PRASETYO ADI (Jurnal Acitya Ardana, 2022)
A non-profit entity is an entity whose main purpose is not to make as much profit as it can but to help the community, and its main resources are obtained from contributions from members and other donors without expecting anything in return. A non-profit entity must prepare financial reports under the standards applicable in each reporting period. This study aims to determine whether the financial statements of the Javanese Christian Church of Ungaran (GKJ Ungaran), as a non-profit entity, are following the terms mentioned in the Statement of Financial Accounting Standards (PSAK) 45. This conformity is determined by comparing the terms contained in PSAK 45 with the financial reporting practices carried out by GKJ Ungaran. The analytical method used is qualitative analysis. The research data used are primary data and secondary data obtained through interviews and documentation. The data analysis technique used is comparative descriptive analysis. The results show that GKJ Ungaran has not carried out its financial reporting activities under the terms contained in PSAK 45. Furthermore, GKJ Ungaran has not made financial reports that are required by PSAK45. In practice, GKJ Ungaran should carry out its financial reporting activities under applicable standards.